Density functional study on the geometric features and growing pattern of B nP m clusters with n = 1-4, m = 1-4, n + m ≤ 5 - Ferraresi Curotto, Verónica (2012)
The bonding features of BnPm clusters (n ¼ 1–4, m ¼ 1–4, n þ m 5) are studied within the framework of the density functional theory following a systematic growing mechanism. Some stable geometries are found to agree well with results reported previously in the literature. Other geometries are found to be more stable than structures reported elsewhere for small B/P aggregates. To the best of our knowledge, stable geometries for BP4 are reported for the first time. It is found that small B/P clusters with up to five atoms tend to grow mainly toward nonlinear bidimensional structures. The existence of BAB and BAP bonds seems to be of importance for the relative stability of clusters as they grow. The growing patterns could be explained mainly in terms of electrophilic attacks of B atoms to BAB and BAP bonds. It is found that the growing is in general accompanied by geometry reorganization and atomic charge rearrangements. Electrophilic attacks of P atoms to BAB bonds seems to be a good alternative to grow for aggregates with many B atoms. Atomic charges derived from molecular electrostatic potentials are useful to understand the growing paths followed in terms of electrophilic or nucleophilic attacks.